Narrative Agency and Structural Chaos. A Biographical-Narrative Case Study - Filipkowski, Piotr (Qualitative Sociology Review, 2019)
The article is an analysis of a single case—a biographical narrative of a Tri-City resident who enters adulthood at the beginning of political transformation in 1989, and whose life path turns out to be an unintentional, dynamic journey between various professions, social worlds and structural positions. This creates a complicated and ambiguous biographical pattern which does not fall into either the socio-economic promotion of the “winner” or into the degradation of the transformation “loser.” The reconstruction of this pattern reveals the hero’s great resourcefulness and entrepreneurship, but also the fragility of the structures stabilizing his life and the volatility of life orientation points. The binder of this biography turns out to be, above all, reflexivity and, what I suggest calling, the narrative agency of the narrator, who can transform his structurally dispersed and chaotic life experiences of the time of transformation into a very original story, making him a strong subject of his own fate. This, however, creates the inevitable tension between the experienced or lived life, life history and the narrated life, life story, prompting us to again pose the question about the commonly assumed, although differently defined, correspondence between the level of reality and the level of its linguistic (in this case—autobiographical) representation.